The impact of a change in work posture from seated to stand‐up on work‐related musculoskeletal disorders among sewing‐machine operators. Issue 8 (6th June 2018) - Grobler, Susan H.; Mostert, Karien; Becker, Piet
Abstract : Background: Work‐related postural change could lead to improved musculoskeletal health. Method(s): In a quantitative, retrospective, longitudinal study, data of work‐related musculoskeletal disorders of 123 sewing‐machine operators were captured for 4.5 years, and analysed using Poisson regression. Results: Stand‐up work posture (SUWP) reduced the incidence for spinal disorders (SD) to 0.29 fold the incidence for sitting work posture (SWP) ( P  < 0.001). Morbid obesity had significantly increased ( P  = 0.04) incidence of upper limb disorders (ULD), 3.35 times that of normal body mass index (BMI) (regardless of work posture). SUWP was associated with increased IRR (1.49) for lower limb disorders (LLD). LLDs were associated with obesity (overweight (IRR = 2.58; P  = 0.08), obese (IRR = 2.45; P  = 0.09), and morbidly obese (IRR = 6.24; P  = 0.001)). Conclusions: The protective benefit of the SUWP was statistically significant for SD incidence. Owing to high mean BMI, SUWP had a negative impact on the incidence of LLDs for the first 2 months.